Honeycomb structure composite material and preparation method and application thereof

The manufacturing of short carbon fiber reinforced honeycomb composite materials through direct write 3D printing technology solves the problems of complex processes and high energy consumption, and realizes the preparation of lightweight, high-strength and low-density materials, meeting the application needs of aerospace and other fields.

CN119682200APending Publication Date: 2025-03-25TIANJIN POLYTECHNIC UNIV +1

Patent Information

Application Number
CN202411926946.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The preparation process of existing honeycomb structure composite materials is complex, has insufficient automation, high energy consumption and poor environmental friendliness, making it difficult to meet the lightweight and high-strength needs in aerospace and other fields.

Method used

The short carbon fiber reinforced honeycomb composite is manufactured using direct-write 3D printing technology, and the ink paste is prepared by mixing and stirring, and printed and cured in the 3D printer according to preset parameters, simplifying the process flow and reducing costs.

Benefits of technology

It has achieved a lightweight, high-strength, low-density honeycomb structure composite material with significant energy absorption capacity and excellent mechanical properties, meeting application needs in aerospace and other fields, while reducing raw material costs and production cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682200A_ABST
    Figure CN119682200A_ABST
Patent Text Reader

Abstract

The invention provides a honeycomb structure composite material and a preparation method and application thereof, and belongs to the technical field of composite materials. The method comprises the following steps: mixing attapulgite, short carbon fibers, bisphenol epoxy resin and an imidazole curing agent through a direct-writing 3D printing technology to prepare ink slurry, printing according to a preset honeycomb structure, and carrying out curing and subsequent drying treatment to prepare the honeycomb structure composite material. The material has the advantages of low density, strong energy absorption capability and excellent mechanical properties, and shows excellent stability in longitudinal compression and tensile tests. Compared with traditional pressing forming, chemical vapor deposition and other processes, the technological process is simplified, the production cycle is remarkably shortened, and the manufacturing cost is remarkably reduced. In addition, the 3D printing technology endows the material with high-precision microstructure control capability, and the honeycomb wall thickness and the grid size and height can be flexibly adjusted, so that the requirements of diversified fields such as aerospace, automobile lightweight and building heat insulation are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a honeycomb structure composite material and a preparation method and application thereof, belonging to the technical field of composite materials. Background Art

[0002] As the demand for weight reduction in spacecraft becomes increasingly urgent, the requirements for applied materials are becoming increasingly stringent. Lightweight structural materials, especially those represented by aluminum alloys, magnesium alloys, titanium alloys and composite materials, have become a hot topic in the aerospace field due to their excellent mechanical properties.

[0003] In recent years, in order to achieve lightweight composite materials, the prior art generally adopts injection molding process to prepare honeycomb structure or porous structure to reduce the density of composite materials and improve their mechanical properties. Honeycomb structure has been widely used in fields such as structural reinforcement and shock absorption due to its light weight, high strength, excellent energy absorption capacity and good thermal properties. The introduction of honeycomb structure in epoxy resin-based composite materials can significantly improve the mechanical properties and structural stability of the material, thereby expanding its application range. At present, the process of preparing honeycomb structure composite materials is mainly through compression molding, chemical vapor deposition and mold molding. For example, patent CN119041807A has problems such as complex process, insufficient automation, high energy consumption and poor environmental friendliness through the steps of resin paste preparation, fiber cutting, pressure impregnation and compression molding. Patent CN119118697A is prepared by chemical vapor deposition, and the vacuum environment and high temperature treatment consume a lot of energy, and the process cycle is long, which further increases the production cost. The preparation process of patent CN117466569B includes multiple steps (such as honeycomb structure cutting, surface etching, aerogel particle processing, slurry injection, curing, etc.). The operation is cumbersome and has strict requirements on process parameters. A slight error may result in the final performance not meeting the standards. Summary of the invention

[0004] The present invention provides a lightweight, high-strength, low-density short carbon fiber reinforced honeycomb composite material structure, which is manufactured by direct writing 3D printing technology, combining the excellent mechanical properties of short carbon fibers with the excellent energy absorption capacity of the honeycomb structure. The composite material can effectively maintain structural integrity under a specific load direction, and exhibits excellent performance under compression and tension, meeting the requirements of mechanical properties and lightweight. At the same time, the preparation method can reduce the cost of raw materials, simplify the process and shorten the production cycle, thereby achieving cost reduction of lightweight and high-performance composite materials. The material can be widely used in aerospace, automobile manufacturing, sports equipment and protective materials and other fields, and has important industrial application value.

[0005] In order to solve the above problems, the first aspect of the present invention provides a carbon fiber reinforced epoxy resin-based honeycomb structure composite material, which comprises, by mass percentage:

[0006] 15% to 30% of attapulgite, 5% to 15% of short carbon fibers, 30% to 60% of bisphenol epoxy resin and 2% to 8% of imidazole curing agent.

[0007] Preferably, the cross-section of the honeycomb structure is a regular hexagon; the honeycomb wall thickness of the honeycomb structure is 0.2-0.6 mm, the side length of the honeycomb grid is 3-8 mm, and the height of the honeycomb grid is 5-15 mm.

[0008] Preferably, the average diameter of the short carbon fibers is 60 to 90 μm; and the average length of the short carbon fibers is 280 to 320 μm.

[0009] Preferably, the imidazole curing agent is one or more of 2-methylimidazole, 2-ethylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole and 2-ethyl-4-methylimidazole.

[0010] A second aspect of the present invention provides a method for preparing the above-mentioned carbon fiber reinforced epoxy resin-based honeycomb structure composite material, comprising the following steps:

[0011] The attapulgite, bisphenol epoxy resin, short carbon fiber and imidazole curing agent are mixed and stirred to obtain ink slurry; the prepared ink slurry is placed in a barrel, printed according to a preset honeycomb structure, and then cured and formed to obtain a carbon fiber reinforced epoxy resin-based honeycomb structure composite material.

[0012] Preferably, the preparation method further comprises:

[0013] Preferably, the ink is stirred for 10 to 15 minutes.

[0014] In the present invention, the 3D printer is preferably a direct writing 3D printer.

[0015] In the present invention, the printing time of the 3D printing is preferably 10 to 25 seconds.

[0016] In the present invention, the printing interval of the 3D printing is preferably 1 to 3 seconds.

[0017] In the present invention, the air pressure of the 3D printing is preferably 240-290 psi.

[0018] In the present invention, the temperature of the cured product is preferably 80 to 120° C., and the curing time is preferably 2 to 4 hours.

[0019] Preferably, after curing and molding, the obtained product is dried. The drying conditions are: first drying at 30-60° C. for 8-12 hours, and then drying at 80-100° C. for 2-4 hours.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a lightweight, high-strength, low-density 3D printed honeycomb structure composite material with significant energy absorption capacity. The short carbon fiber reinforced honeycomb structure exhibits excellent mechanical properties under longitudinal compression and tension. Since the short carbon fiber is anisotropic, its mechanical properties vary significantly in different loading directions. The epoxy resin-based composite material reinforced by the honeycomb structure has an extremely low material density, which can be between 0.4 and 0.8 g / cm 3 The thermal transfer and mechanical properties are significantly better than those of traditional resin-based composites.

[0022] The present invention uses direct writing 3D printing for one-step molding, avoiding the multi-step operations (such as mold molding, pouring and curing, etc.) in the preparation of traditional honeycomb structure composite materials, and significantly simplifying the process flow. Through direct writing 3D printing technology, the honeycomb wall thickness, lattice size and honeycomb height can be flexibly designed to meet the structural requirements of diversified application scenarios. Direct writing 3D printing achieves high-precision control of the internal microstructure of the material, avoiding the performance inconsistency problem caused by error accumulation in traditional mold preparation. While meeting the lightweight and high-strength requirements in the aerospace field, it also provides a solution for the rapid manufacture of lightweight, high-performance structural materials in other fields (such as automobiles and construction). BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A roadmap for direct-write 3D printing of honeycomb composites;

[0024] Figure 2 It is a schematic diagram of the forces acting on the composite material products of the embodiment of the present invention and the comparative example;

[0025] Figure 3 A tensile stress-strain comparison diagram of the composite material product of the embodiment of the present invention and the comparative example;

[0026] Figure 4 It is a compressive stress-strain comparison diagram of the composite material products of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the present invention, not all embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in the field without creative work all belong to the scope of protection of the present invention.

[0028] Example

[0029] In the following Example 1, Comparative Example 1 and Comparative Example 2, short carbon fibers were purchased from Zhongfu Shenying Co., Ltd., with an average diameter of 60 to 90 μm and an average length of 280 to 320 μm. Attapulgite was purchased from Shenzhen Shunmei Co., Ltd., with a purity greater than 90%. Bisphenol epoxy resin and imidazole curing agent were purchased from Kunshan Green Shield Chemical Co., Ltd., and mold release agent was purchased from Walkerson Corporation of the United States.

[0030] Example 1

[0031] This embodiment 1 relates to a method for preparing a 3D printed honeycomb structure reinforced epoxy resin-based composite material, comprising the following steps:

[0032] SolidWorks software was used to establish a model suitable for tensile and compression tests. The honeycomb wall thickness, honeycomb grid side length, and honeycomb grid height of the honeycomb structure were set to 0.5 mm, 6 mm, and 13 mm, and the model was exported to ISO format.

[0033] 25% of attapulgite, 10% of short carbon fiber, 60% of bisphenol epoxy resin and 5% of 2-ethylimidazole curing agent were mixed and stirred for 10 minutes to prepare resin-based ink. Then, the ink was loaded into the barrel and printed according to the set parameters.

[0034] Set the printing time of 3D printing to 20s.

[0035] Set the printing interval of 3D printing to 2s.

[0036] Set the air pressure for 3D printing to 260 psi.

[0037] Apply the release agent to the glass slide once every 6 minutes. Allow to dry for 5 minutes after each application. Usually apply twice.

[0038] The printed honeycomb structure composite material product was cured at a curing temperature of 100° C. and a curing time of 2 h.

[0039] After curing and molding, the obtained product is dried under the following drying conditions: first drying at 50° C. for 9 h, and then drying at 80° C. for 2 h.

[0040] The density of the honeycomb structure reinforced resin-based composite material obtained by 3D printing is 0.48g / cm 3 , thermal conductivity is 0.089W / (m·K). The tensile strength and compressive strength of the material both reach the maximum value, and all performances meet the design and use requirements.

[0041] In addition, the preparation method of this embodiment 1 has the advantages of short production cycle and low cost. The prepared honeycomb structure not only has strong bearing capacity and delicate structure, but also can effectively disperse external forces from all directions.

[0042] Comparative Example 1

[0043] This comparative example 1 relates to a method for preparing an injection-molded honeycomb structure composite material, comprising the following steps:

[0044] A honeycomb structure mold was made, with a honeycomb wall thickness of 0.5 mm, a honeycomb lattice side length of 6 mm, and a honeycomb lattice height of 13 mm.

[0045] 25% silica, 10% short carbon fiber, 60% epoxy resin and 5% 2-ethylimidazole curing agent were mixed and stirred for 10 minutes to prepare a resin-based ink, which was then injected into the prepared honeycomb structure mold and sealed.

[0046] The finished honeycomb structure composite material formed by the mold is cured at a curing temperature of 100° C. and a curing time of 2 hours.

[0047] After curing and molding, the obtained product is dried under the following drying conditions: first drying at 50° C. for 9 h, and then drying at 80° C. for 2 h.

[0048] The density of the injection molded honeycomb structure reinforced resin matrix composite material is 0.54 g / cm 3 , thermal conductivity is 0.066W / (m·K). The tensile strength and compressive strength of this material are relatively weak.

[0049] Comparative Example 2

[0050] This comparative example 2 relates to a method for preparing a 3D printed square structure reinforced epoxy resin composite material, comprising the following steps:

[0051] SolidWorks software was used to establish a model suitable for tensile and compression tests. The wall thickness, side length, and height of the square structure were set to 0.5 mm, 5 mm, and 13 mm, and then exported to ISO format.

[0052] The resin-based ink was prepared by mixing 25% silica, 10% short carbon fiber, 60% epoxy resin and 5% 2-ethylimidazole curing agent for 10 minutes. The ink was then loaded into the barrel and printed according to the set parameters.

[0053] Set the printing time of 3D printing to 20s.

[0054] Set the printing interval of 3D printing to 2s.

[0055] Set the air pressure for 3D printing to 260 psi.

[0056] Apply the release agent to the glass slide once every 6 minutes. Allow to dry for 5 minutes after each application. Usually apply twice.

[0057] The printed square structure composite material product was cured at a curing temperature of 100°C and a curing time of 2 hours.

[0058] After curing and molding, the obtained product is dried under the following drying conditions: first drying at 50° C. for 9 h, and then drying at 80° C. for 2 h.

[0059] The density of the square structure reinforced resin-based composite material obtained by 3D printing is 0.63g / cm 3 , the thermal conductivity is 0.056W / (m·K). The tensile strength and compressive strength of this material are not as good as those of 3D printed honeycomb structure composite materials.

[0060] In the preparation method of this comparative example 2, short carbon fibers are evenly distributed in the composite material, which has the advantages of short production cycle and low cost. However, the stability of the square structure is not as good as that of the honeycomb structure, and its tensile and compressive resistance is poor.

[0061] Although the above embodiments have been described in detail, they are only some embodiments of the present invention, not all embodiments. Technicians can derive other embodiments based on these embodiments without creative work, and these embodiments all belong to the protection scope of the present invention.

Claims

1. A method for preparing a honeycomb structure composite material, characterized in that: The following steps are involved: 15% to 30% of attapulgite, 5% to 15% of short carbon fiber, 30% to 60% of bisphenol epoxy resin and 2% to 8% of imidazole curing agent are mixed and stirred according to mass percentage to obtain ink slurry; the ink slurry is loaded into the barrel of a direct writing 3D printer, and printing is performed according to the set honeycomb structure parameters; After printing is completed, the honeycomb structure material is cured at 80 to 120° C. for 2 to 4 hours; the cured material is dried in turn.

2. The method for preparing the honeycomb structure composite material according to claim 1, characterized in that: The cross section of the honeycomb structure is a regular hexagon, the honeycomb wall thickness is 0.2-0.6 mm, the honeycomb grid side length is 3-8 mm, and the honeycomb grid height is 5-15 mm.

3. The method for preparing the honeycomb structure composite material according to claim 1 or 2, characterized in that: The average diameter of the short carbon fibers is 60 to 90 μm, and the average length is 280 to 320 μm.

4. The method for preparing the honeycomb structure composite material according to claim 1 or 2, characterized in that: The imidazole curing agent includes one or more of the following: 2-methylimidazole, 2-ethylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 2-ethyl-4-methylimidazole.

5. The method for preparing the honeycomb structure composite material according to claim 1, characterized in that: The ink slurry is stirred for 10 to 15 minutes.

6. The method for preparing the honeycomb structure composite material according to claim 1, characterized in that: The printing time of the 3D printing is 10 to 25 seconds, the printing interval is 1 to 3 seconds, and the printing pressure is 240 to 290 psi.

7. A honeycomb structure composite material, characterized in that: The preparation method is as described in any one of claims 1 to 6.

8. The honeycomb structure composite material according to claim 7, characterized in that: Density: 0.4~0.8g / cm 3 , thermal conductivity is less than 0.1W / (m·K).

9. The honeycomb structure composite material according to claim 8, characterized in that: It exhibits excellent mechanical properties in longitudinal compression and tension tests, with significant energy absorption capacity and high structural integrity.

10. Use of the honeycomb structure composite material according to claims 7-9, characterized in that: The honeycomb structure composite material is applied to the fields of aerospace, automobile lightweighting, building structure reinforcement and thermal insulation.

Citation Information

Patent Citations

  • A honeycomb structure reinforced aerogel-phenolic resin based composite material and preparation method thereof

    CN117466569B

  • Honeycomb structure double-leaf airtight door made of SMC glass fiber reinforced composite material

    CN119041807A

  • Preparation method of fiber-reinforced ceramic-based / carbon-based composite material honeycomb structure

    CN119118697A

Cited By

  • Composite material 3D printing forming method based on cooperative regulation and control of path and process parameters

    CN120516953A